The Influence Of Profitability, Liquidity, Leverage , And Activities On The Timeliness Of Submitting Financial Statements - Budiantoro, Harry; Yuniar Fachriawati Fauzi; Kanaya Lapae (SEAN Institute, 2022)
This study aims to see the effect of profitability, liquidity, leverage, and activity ratios on the timeliness of financial statement submission. The population of this study were food and beverage companies listed on the Indonesia Stock Exchange (IDX) between 2013 and 2017. The sample was taken by purposive sampling with 85 samples. Quantitative research methods used. Secondary data, especially the company's annual financial statements obtained from the official website of the IDX, are used in the sampling technique. Logistic regression analysis method was used with SPSS version 25.0. The findings show that profitability, liquidity, leverage, and activity ratios all have a significant impact on the timeliness of financial statement submissions. partially, the activity ratio variable affects the timeliness of financial report submission. While the variables of profitability, liquidity and leverage have no effect on the timeliness of submitting financial statements.